Causal Factors Influencing Indebtedness of Undergraduate Students in Bangkok - Intaravorraphat, Phonphat; Chetsumon, Sireerat; Traimongkolkul, Pongpan (Kasetsart Journal of Social Sciences, 2014)
Household debt has become a national crisis in Thailand. Among college students, it was found that student loan debt has increased in recent years. The situation is getting worse when the students are involved in non-student loan debt. This study investigated the causal factors influencing non-student loan indebtedness of undergraduate students in Bangkok. Using a multi-stage sampling technique, a sample size of 1,601 undergraduate students was randomly selected from five universities in Bangkok. A structural equation model was developed to explore the pattern of relationships among the aforementioned factors. As a whole, the amount of debt was positively influenced by expected future income after graduation, student expenditure, perceived utility of a bachelor’s degree, consumerism behavior, attitude towards economic situation, financial stress, household income, attitude towards indebtedness, and student’s purchasing power (assets, total savings, and income), in rank order. On the other hand, the amount of debt was negatively influenced by competency on the Philosophy of Sufficiency Economy, the student’s financial learning, savings per month, perceived utility of saving money, and financial management, in rank order. All these causal factors accounted for 41 percent of the variance explained by the amount of debt (R2= 0.41, p <.05).